Hollow Ratio and Stiffeners Effects Concrete Filled Double Steel Tubes Behaviour - Amin Gholizad (Iranian Society of Structrual Engineering (ISSE), 2015)
Concrete Filled Double Steel Tubes are mostly used in bridge piers, tall buildings, offshore and coastal structures and power transmission towers. Finite element analyses via ABAQUS software have been performed aiming to evaluate the strength, ductility and plastic deformation of CFDST columns with different hollow ration and stiffeners configurations. According to analyses results more strength and high ductility levels can be provided decreasing the composite section hollow and increasing stiffeners thickness. More stiffener plates with larger dimensions result in more strength and stiffness in composite columns due to increase in concrete confinement and adjoint interaction of steel and concrete. It also raises plastic deformation level of the columns and postpone the local buckling.